On the development of physical qualities and improving the health of University students - Nurmatova D. R. (Education and science in the modern context, 2017)
the article examines the essence and main components of the process of physical education in high school, recommendations for improvement and practical development of students of the subject material, to promote health and improve educational performance.
Keywords: личность; физическая культура; физическая подготовка; тренировка; training; Personality; школьник; student; Physical culture; физические способности; physical abilities; physical preparation